(3GSJNOGe GdhGdOjf GdeaQW dhSGFd GdJhGUd GdGLJeGYi GdMOjKI hCKQg ai cd ef GdefGN GdCSQi heOi ETHGY GdMGLGJ GdfaSjI ddCHfGAs - (3gGjOi feQ eMeO QVhGf,s; (3eUWai CMeO JQcis (2022)
(3gOaJ gPg GdOQGSI Gdi GdcTa Yf GSJNOGe GdhGdOjf GdeaQW dhSGFd GdJhGUd GdGLJeGYi GdMOjKI hCKQg ai cd ef GdefGN GdCSQi ceG jOQcg GdCHfGA heOi ETHGY HYV GdMGLGJ GdfaSjI dgDdGA GdCHfGA(B. (3hbO JchfJ YjfI GdOQGSI ef (B((3f(B-100) (3Wad eef HdZ GYeGQge (B11-12 (3YGeG ef eQMdI GdWahdI GdeJCNQI, hGSJNOeJ GdOQGSI ebjGS EaQGW GdhGdOjf ai GSJNOGe hSGFd GdJhGUd GdGLJeGYi GdMOjKI EYOGO GdHGMKI, hebjGS GdefGN GdCSQi EYOGO GdHGMKI, hebjGS GTHGY GdMGLGJ GdfaSjI EYOGO GdHGMKI, hCXgQJ GdfJGFL HCfg JhLO aQhb PGJ OdGdI GMUGFjI Hjf eJhSWi OQLGJ GHfGA GdeLehYJjf GdeaQWI hZHQ GdeaQWI ai GSJNOGe hSGFd GdJhGUd GdELJeGYi GdMOjKI ai GdefGN GdCSQi hai eOi GTHGY HYV GdMGLGJ GdfaSjI, hLGAJ eJhSWGJ GdeLehYI ZjQ GdeaQWI ai GSJNOGe hSGFd GdJhGUd GdGLJeGYi GdMOjKI GcHQ ef eJhSWGJ GdeLehYI GdeaQWI ai cd ef GdefGN GdCSQi, heOi GTHGY HYV GdMGLGJ GdfaSjIs
(3CWQhMI (B((3OcJhGQg(B)-(3LGeYI GdbGgQI, (B2022.s
(3HHdjhLQGajG(B: (3U(B. 113-123.s
Keywords: (3GdCHGA hGdCHfGAs; (3hSGFd GdJhGUd GdELJeGYis